2014
DOI: 10.4236/ojn.2014.44038
|View full text |Cite
|
Sign up to set email alerts
|

Kindergarten Teacher’s Knowledge of Enterobiasis in Korea

Abstract: Previous reports have suggested that the environment of day care centres is a crucial factor in the development of enterobiasis. There is a lack of data regarding a teacher's knowledge about enterobiasis although kindergarten teachers have the greatest influence on a child's habits because the child spends a lot of time with them and because they manage the child's physical environment. The focus of the present study was to evaluate the kindergarten teacher's level of knowledge regarding enterobiasis. The cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
(19 reference statements)
0
2
1
Order By: Relevance
“…Our research found that scores of child health knowledge of female preschool teachers were lower than male preschool teachers, which was different from the results without gender difference in other health knowledge scores or awareness of other preschool teachers, 31 , 35 , 36 , 38 , 45 , 46 but was similar to the results of a study in Greece regarding health knowledge of infant diabetes. 47 This finding suggests that male teachers may possess greater health knowledge in the group of preschool teachers, and it may also be due to the fact that male preschool teachers in China act as physical education teachers or health education personnel in kindergartens, and as a result, their health knowledge scores are higher.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our research found that scores of child health knowledge of female preschool teachers were lower than male preschool teachers, which was different from the results without gender difference in other health knowledge scores or awareness of other preschool teachers, 31 , 35 , 36 , 38 , 45 , 46 but was similar to the results of a study in Greece regarding health knowledge of infant diabetes. 47 This finding suggests that male teachers may possess greater health knowledge in the group of preschool teachers, and it may also be due to the fact that male preschool teachers in China act as physical education teachers or health education personnel in kindergartens, and as a result, their health knowledge scores are higher.…”
Section: Discussioncontrasting
confidence: 99%
“…As the previous studies showed that sociodemographic characteristics and health-related arrangements and kindergarten regulations may have different effects on the knowledge. 22,[31][32][33] The following set of models was used: (i) Model 1 adjusted for sociodemographic characteristics, which include gender, fertility status, age, education level, marital status, working years, monthly income, BMI, and satisfaction with health; (ii) Model 2 adjusted for health-related arrangements and kindergarten regulations, which include supportive measures for kindergartens and (iii) Model 3 further adjusted for all variables in Model 1 and Model 2. After analysis, it was determined that Model 3 was the most optimal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation